The Effect of Cold Compress Therapy and Breastfeeding on Reducing Pain in Infants During Immunization (PCV) at Separi III Public Health Center - Nisfu Nurjanah; Chandra Sulistyorini; Hestri Norhapifah; Dwi Ida Puspitasari (Journal of Global Research in Public Health, 2025)
In Indonesia, from from 2017 to 2021, there were 1,525,936 children Not yet get immunization base complete, at the Health Center Separi III coverage immunization base complete in 2023 is 83.4 % coverage low immunization is PCV with results baby who has do PCV 1 immunization 73.9%, PCV 2 62.6%. (Health Center Separi III, 2023) . Immunization is effort give immunity body to disease certain conditions, especially in vulnerable infants and children. to infection. Pain and anxiety moment immunization often become obstacle for parents for finish timetable immunization children they . Research This aiming For know influence combination therapy compress cold and breastfeeding decline pain in babies moment PCV immunization at the Community Health Center Separi III. Method: Study This use method quasi- experimental with posttest only non-equivalent control group design. Samples were taken in a way non probability sampling with total sampling technique, involving 34 babies who were divided into two groups. Group intervention accept therapy compress cold and breastfeeding, while group control only accept cotton Disinfection level high (DTT) according to procedure Health Center. Results: Research results show existence decline intensity pain in babies moment immunization from painful heavy become painful medium, light, even no painful the same once. Data analysis using Mann Whitney Test show p-value of 0.000 (p < 0.05), indicates that There is influence significant combination therapy compress cold and breastfeeding decline pain in babies moment PCV immunization. Conclusion and Suggestions: Combination therapy compress cold and effective breastfeeding in reduce intensity pain in babies moment PCV immunization, so that can become a recommended strategy in practice immunization For increase comfort and reduce anxiety in babies and parents.